Pendekatan Spasial dalam Perencanaan Lanskap Kampung Wisata Jamburea di Kabupaten Garut - Alfarisi, Gema Febri; Damayanti, Vera D (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023, 2023)
Spatial Appro ach in Landscape Planning for Jamburea Tourism Village in Garut Regency. Jamburea, located in the Banyuresmi District of Garut, is a potential tourist haven with its unique blend of natural beauty and rich cultural traditions. Dominated by wetland landscapes influenced by the seasonal Situ Rancakukuk lake, residents adapt by converting its periphery into rice fields during the dry season and fish ponds during the rainy season. Furthermore, the kampong region is a repository of intangible cultural assets, such as culinary speciality, Pencak silat, traditional children’s games, 'Asgar' barber shops, and bamboo handicrafts. Employing ArcGIS tools, this study used a spatial approach to analyze physical-biophysical, non-physical, and tourism aspects for optimal zoning. This paper has two objectives: firstly, to plan the landscape of the Jamburea tourism village using a spatial approach in the analytical process. The second objective is to examine the application of spatial methods in landscape planning. Results suggest 72.09% of the kampong is suitable for tourism development, 13.68% is moderately suitable, and 14.23% requires conservation. Proposed zones include natural and cultural tourism, tourism support, welcome areas and buffer zones. This study underscores the efficacy of the spatial approach in devising comprehensive plans for Jamburea's tourism potential.